Towards understanding desert shorelines - coastal landforms and dynamics around ephemeral Lake Eyre North, South Australia. Issue 1 (2nd January 2022) - May, Jan-Hendrik; May, S.M.; Marx, S.K.; Cohen, T.J.; Schuster, M.; Sims, A.
ABSTRACT: While shorelines around playa lakes have traditionally played a key role for reconstructing late Quaternary megalakes in drylands, little attention has been given to recent shorelines associated with episodic filling events of modern ephemeral playa lakes such as Kati Thanda-Lake Eyre in central Australia. We here present results from geomorphic mapping around the playa margin of Lake Eyre North and interpret these data regarding timescales and drivers of shoreline processes. The diversity and distribution of landforms point to lithology and variations in wave energies as major controls on large-scale shoreline geomorphology. Our results suggest that the presence or absence of shoreline features is an incomplete and inaccurate indicator of past lake levels. Instead, wave-built landforms in ephemeral playa lake settings need to be considered threshold-related phenomena, with differences in frequency, magnitude and rate of water level change leading to vertically differing potential for wave-driven geomorphic activity and thus topographic differences between landforms. While mainland barriers probably best represent rare peak lake levels, barrier spits or islands dominantly form at lower and intermediate levels through lower energy longshore drift, thus providing a more complete record of playa flood events. Additionally, the lowest magnitude events offer potential for frequent wetting and drying along playa margins that effectively drives salt-related production and aeolian sediment deflation. Therefore, in contrast to marine or perennial lake shorelines, the complete range of wind-driven sedimentary processes needs to be coupled with an accurate understanding of lake-specific flooding frequency and magnitude towards a comprehensive model of shoreline evolution around playa lakes.